Cover Feature: Cubane Electrochemistry: Direct Conversion of Cubane Carboxylic Acids to Alkoxy Cubanes Using the Hofer–Moest Reaction under Flow Conditions (Chem. Eur. J. 2/2020). Issue 2 (19th November 2019) - Collin, Diego E.; Folgueiras‐Amador, Ana A.; Pletcher, Derek; Light, Mark E.; Linclau, Bruno; Brown, Richard C. D.
Abstract : Cubane has been known about for more than half a century, but methods for direct functionalization of commercial cubane derivatives remain somewhat limited. The possibility of using electrochemical methods to transform cubane carboxylic acids presented an intriguing possibility, leading to the development of anodic decarboxylative ether formation in flow. The image, created by Noémie Collin, shows an ammonite fossil merged with an "Ammonite" flow electrolysis cell; electricity drives oxidation of the carboxylate functionality to form cubyl ethers. More information can be found in the Communication by B. Linclau, R. C. D. Brown, et al. on page 374 .